Toxicity of four veterinary pharmaceuticals on the survival and reproduction of Folsomia candida in tropical soils - Zortea T.* (2017)
© 2017 Elsevier LtdThis study aimed to evaluate the effect of veterinary pharmaceuticals (VPs) used to control endo- and ectoparasites in ruminants, on the survival and reproduction of the collembolan species Folsomia candida. Standard ecotoxicological tests were conducted in Tropical Artificial Soil and the treatments consisted of increasing dosages of four commercial products with different active ingredients: ivermectin, fipronil, fluazuron and closantel. Ecotoxicological effects were related to the class and mode of action of the different compounds. Fipronil and ivermectin were the most toxic compounds causing a significant reduction in the number of juveniles at the lowest doses tested (LOECreprodvalues of 0.3 and 0.2 mg kg−1of dry soil, respectively) and similar low EC50values (fipronil: 0.19 mg kg−1dry soil, CL95%0.16–0.22; ivermectin: 0.43 mg kg−1dry soil, CL95%0.09–0.77), although the effects observed in the former compound were possibly related to a low adult survival (LC50of 0.62 mg kg−1dry soil; CL95%: 0.25–1.06). For the latter compound no significant lethal effects were observed. Fluazuron caused an intermediate toxicity (EC50of 3.07 mg kg−1dry soil, CL95%: 2.26–3.87), and also here a decrease in adult survival could explain the effects observed at reproduction. Closantel, despite showing a significant reduction on the number of juveniles produced, no dose-response relationship nor effects higher than 50% were observed. Overall, all tested compounds, especially ivermectin, when present in soil even at sub-lethal concentrations, can impair the reproduction of collembolans and possibly other arthropods. However, the actual risk to arthropod communities should be further investigated performing tests under a more realistic exposure (e.g., by testing the dung itself as the contaminated matrix) and by deriving ecotoxicologically relevant exposure concentration in soil derived from the presence of cattle dung.